2021
DOI: 10.1002/ptr.7038
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of short‐term bilberry supplementation on glycemic control, cardiovascular disease risk factors, and antioxidant status in Chinese patients with type 2 diabetes

Abstract: Bilberry (Vaccinium myrtillus L.) is one of the richest natural sources of anthocyanins which are powerful antioxidants and reported to have antiinflammatory, antidyslipidemic, antihypertensive, and hypoglycemic effects. The objective of this study was to assess the effect of bilberry supplementation on biomarkers of glycemic control, lipid profile, antioxidant, and inflammatory status in patients with type 2 diabetes in a randomized, double-blind, placebo-controlled cross-over study. Twenty patients were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 68 publications
(79 reference statements)
0
47
0
Order By: Relevance
“…Cardiometabolic diseases ranged from hypertension, myocardial infarction, metabolic syndrome, overweight/obesity, and non‐alcoholic fatty liver disease. The length of intervention ranged from four (Chan et al, 2021; Dohadwala et al, 2011; Ruel et al, 2013) to 24 weeks (Curtis et al, 2019; Masnadi Shirazi et al, 2021). Fifteen studies were randomized, double‐blind, or triple‐blind, while two were only randomized (Arevström et al, 2019; Basu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiometabolic diseases ranged from hypertension, myocardial infarction, metabolic syndrome, overweight/obesity, and non‐alcoholic fatty liver disease. The length of intervention ranged from four (Chan et al, 2021; Dohadwala et al, 2011; Ruel et al, 2013) to 24 weeks (Curtis et al, 2019; Masnadi Shirazi et al, 2021). Fifteen studies were randomized, double‐blind, or triple‐blind, while two were only randomized (Arevström et al, 2019; Basu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 20 (Lee et al, 2008) to 115 subjects (Curtis et al, 2019). Eight studies used cranberry as an intervention (Basu et al, 2011; Dohadwala et al, 2011; Eftekhari et al, 2016; Hsia et al, 2020; Lee et al, 2008; Masnadi Shirazi et al, 2021; Richter et al, 2021; Ruel et al, 2014), while the other nine used blueberry (Arevström et al, 2019; Basu et al, 2010; Chan et al, 2021; Curtis et al, 2019; Johnson et al, 2015; Rousseau et al, 2021; Stote et al, 2020; Stull et al, 2010. 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Three human interventions investigated the effect of bilberry consumption on BP. Daily administration of a 1.4 g dose of bilberry extract for four weeks to a group of 20 participants with T2DM, in a double-blind, placebo-controlled, crossover intervention, did not significantly affect SBP or DBP [72].…”
Section: Bilberrymentioning
confidence: 85%
“…However, other clinical studies have indicated that there were no significant differences in fasting plasma glucose between the treatment and the control groups after dietary supplementation with anthocyanins for 12 ( Qin et al, 2009 ) or 24 weeks ( Zhu et al, 2013 ), or after ingesting 400 g fresh bilberries daily for 2 months ( Kolehmainen et al, 2012 ). Even the newest clinical study on Chinese patients with T2DM using 1400 mg of bilberry extract per day did not report any significant differences compared to placebo in any of the measured biomarkers ( Chan et al, 2021 ).…”
Section: Uses Of Vaccinium Myrtillus Lmentioning
confidence: 97%